2020
DOI: 10.5114/ms.2020.94082
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of pentraxin 3 (PTX3) as a biomarker of acute pancreatitis and pancreatic cancer

Abstract: Introduction: Increased concentrations of pentraxin 3 (PTX 3) were diagnosed in acute pancreatitis (AP) and in pancreatic ductal adenocarcinoma (PDAC). Aim of the research: To assess of the clinical usefulness of PTX3 in the early differentiation of AP from PDAC. Material and methods: The test group consisted of 125 patients with AP and 24 people with PDAC, as well as 52 healthy subjects. The following concentrations were tested in plasma: PTX3, C-reactive protein (CRP), interleukin-6 (IL-6), and CA-19.9. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A 2020 study also showed a significant difference in CRP levels between PDAC and normal controls; however, after running extensive statistical tests on all candidate biomarkers it was not included in the final panel of six biomarkers ( 82 ). While CRP is increased in patients with PDAC compared with controls, it is also elevated in patients with moderate and severe pancreatitis ( 83 ). Moreover, as CRP is derived from the liver, it is substantially influenced by the presence of jaundice making it unreliable in patients with this comorbidity ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…A 2020 study also showed a significant difference in CRP levels between PDAC and normal controls; however, after running extensive statistical tests on all candidate biomarkers it was not included in the final panel of six biomarkers ( 82 ). While CRP is increased in patients with PDAC compared with controls, it is also elevated in patients with moderate and severe pancreatitis ( 83 ). Moreover, as CRP is derived from the liver, it is substantially influenced by the presence of jaundice making it unreliable in patients with this comorbidity ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many authors described PTX3 as a potential biomarker of the acute phase in various clinical settings. Serum PTX3 levels were shown to correlate with progression of autoimmune diseases (childhood-onset systemic lupus erythematosus (Quismorio Jr. & Quismorio, 2018), juvenile idiopathic arthritis, atopic dermatitis (Marseglia et al, 2012)), degenerative disorders, arteritis (Hajishengallis & Russell, 2015), and a variety of cardiovascular diseases (Cieślik & Hrycek, 2012;Inoue et al, 2012), as well as acute pancreatitis (Gluszek et al, 2020) and appendicitis (Ates et al, 2020). Studies conducted in neonates revealed that PTX3 is a good biomarker of early-onset sepsis (Densen & Ram, 2015;Baumert et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…PTX3 may serve as a marker for predicting the severe progression of AP, but its clinical utility in differentiating PDAC was not confirmed. [124] Plasminogen activator inhibitor 1…”
Section: Clinical Studiesmentioning
confidence: 99%